Hypothalamic disconnection caudal to paraventricular nucleus affects cardiovascular and drinking responses to central angiotensin II and carbachol - Urzedo-Rodrigues, Lilia Simone; Depieri, Tatiane; Cherobino, Anderson Julio; Lopes, Oswaldo U.; Menani, José Vanderlei [UNESP]; Colombari, Debora S. A. [UNESP] (Elsevier B.V., 2011)
The paraventricular nucleus of the hypothalamus (PVN) is an important area of the brain involved in the control of cardiovascular system and fluid-electrolyte balance. In the present study we evaluated the effects of hypothalamic disconnection (HD) caudal to PVN in the pressor and dipsogenic responses induced by intracerebroventricular (icy) injections of angiotensin II (ANG II) or carbachol (cholinergic agonist). Male Holtzman rats (280-320 g) with a stainless steel cannula implanted into the lateral ventricle and submitted to sham or D surgery were used. HD (2 or 15 days) reduced the pressor responses to ANG II (50 ng/1 mu l) icy (8 +/- 3 and 11 +/- 3 mm Hg, respectively, vs. sham: 23 +/- 3 and 21 +/- 2 mm Hg) or carbachol (4 nmol/1 mu l (8 +/- 2 and 21 +/- 3 mm Hg, respectively, vs. sham: 33 +/- 3 and 33 +/- 3 mm Hg), without changing baseline arterial pressure. Acutely (2-4 days), HD also reduced water intake to icy ANG II (3.3 +/- 2.2 vs. sham: 14.2 +/- 3.0 ml/60 min) or carbachol (4.4 +/- 1.8 vs. sham: 11.4 +/- 1.6 ml/60 min); however, chronically (15-17 days), HD produced no change on ANG II-and carbachol-induced water intake, in spite of the increased daily water intake and urinary volume. The results suggest that medial projections caudal to PVN are important for pressor and dipsogenic responses to central angiotensinergic and cholinergic activation. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Blood pressure; Thirst; Paraventricular nucleus of hypothalamus; Vasopressin; Knife-cut